Assessing carnosinase 1 activity for diagnosing congenital disorders of glycosylation - Interdonato, Livia; Himmelreich, Nastassja; Garbade, Sven; Wen, Dan; Morath, Marina; Di Paola, Rosanna; Calabrese, Vittorio; Thiel, Christian; Peters, Verena (Molecular genetics and metabolism, 2024)
Diagnosing Congenital Disorders of Glycosylation (CDG) is challenging due to clinical heterogeneity and the limited sensitivity of the classic serum transferrin isoelectric focusing (IEF) or capillary zone electrophoresis test. This study investigates the potential of using the glycoprotein carnosinase 1 (CN1) activity as a diagnostic marker for CDG patients. CN1 activity was measured photometrically in serum from 81 genetically confirmed CDG patients and healthy individuals. While the IEF transferrin method detected 77 patients, four remained undetected. In healthy individuals, serum CN1 activity ranged from 0.1 to 6.4 μmol/ml/h depending on age, with mean CN1 activities up to four-fold higher than in CDG patients. CDG patients´ CN1 activities never exceeded 2,04 μmol/ml/h. Using the 25th percentile to differentiate between groups, the test performance varied by age. For children over 10 years old, the sensitivity and specificity were 96 % and 83 %, respectively. For those under 10, sensitivity and specificity dropped to 71 % and to 64 %. However, CN1 activity successfully identified three of four patients with normal IEF patterns. Although mean CN1 activity in CDG patients is significantly lower than in healthy controls, the test's reliability for classic CDG diagnosis is limited, as the diagnosis is usually made at a young age. Nevertheless, it is a simple, cost-effective assay that can complement classic tests, especially in settings with limited access to complex methods or for patients with normal transferrin patterns but suspicious for CDG.
Online verfügbar 30 August 2024, Version des Artikels 3 September 2024
Gesehen am 17.02.2025